Turnover Intention, Kepuasan dan Motivasi Dalam Upaya Meningkatkan Produktivitas Kerja Karyawan OS (out source) Pada PT. PLN (persero) ULP Medan Selatan - Natasya; Ade Indah Sari; Indra Syafii (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine whether Turnover Intention, satisfaction and motivation have a significant effect in increasing work productivity of OS (Out Source) employees at PT. PLN (Persero) ULP South Medan. The typeof research used is associative with a quantitative approach using data analysis techniques of data quality test,classical assumption test, multiple linear regression analysis, and hypothesis testing. The population in thisstudy was 95 OS employees (Out Source). The research sample used a total sampling technique, therefore theresearch sample was 95 people which included all OS employees (Out Source). The results of this study indicatethat the Turnover Intention variable partially has a positive and significant effect in increasing employee productivity, the satisfaction variable partially has a positive and significant effect in increasing employeeproductivity, and the motivation variable partially has a positive and insignificant effect in increasing employeeproductivity. and simultaneously Turnover Intention, satisfaction and motivation have a positive and significanteffect in an effort to increase work productivity of OS (Out Source) employees at PT. PLN (Persero) ULP SouthMedan.